Regression analysis to predict growth performance from dietary net energy in growing-finishing pigs - Sureemas Nitikanchana; Steven S Dritz; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Bradley J White; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2013)
Energy concentration in livestock feed is often altered to optimize pig growth performance and feed cost; therefore, an accurate prediction of growth performance as affected by feeding different energy levels is crucial. Data from 41 trials from 17 journal articles, 10 technical memos, and a thesis were used to develop a regression equation to predict ADG or gain to feed (G:F) as influenced by BW and NE content. Linear and quadratic terms of NE, average BW, CP, standardized ileal digestible [SID] lysine, crude fiber, NDF, ADF, fat, and ash, including their interaction terms, were the variables in the regression analysis. Our regression analysis showed that improvements in growth rate and feed efficiency could be obtained by increasing dietary NE across a wide variety of trials with different dietary ingredients and under different environmental conditions, but the magnitude of improvement in growth performances by dietary NE can be minimized if the amino acids are limiting. Regression equations from this paper can be used to predict the influence of dietary NE on ADG and G:F; however, these equations still need validation from growth studies not included in their development.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Growth performance; Finishing pig; Net energy; Regression